Réponses

2013-04-21T16:10:20+02:00

1) xI = (-5 + 1)/2 = -2
    yI = (6 - 4)/2 = 1

   

    xJ = (7+1)/2 = 4
    yJ = (10-4)/2 = 3

 

2) a. (CI): y = ax + b
            a = (10 - 1)/(7 + 2) = 1
                   10 = 7 + b
                     b = 3
           (CI): y = x + 3


   b. (AJ): y = a'x + b'
            a' = (6 - 3)/(-5 - 4) = - 1/3
                       3 = -1/3 (4) + b'
                      b' = 13/3
             (AJ): y = -x/3 + 13/3

3) -xG/3 + 13/3 = xG + 3
                4xG/3 = 4/3
                      xG = 1
                     yG = 4
   G est le centre de gravité de ABC